Wearable electronic textiles. Issue 4 (2nd October 2019) - Tyler, David; Wood, Jane; Sabir, Tasneem; McDonnell, Chloe; Sayem, Abu Sadat Muhammad; Whittaker, Nick
Abstract: Whilst the bulk of products classified as wearable technologies are watch-like bands that are worn on arms and legs, there is growing interest not only in garments that incorporate sensors and actuators, but also in sensors and actuators that are textile-based. The vision is for information-gathering garments where the electronic components are both inconspicuous and comfortable, and where the data gathered is integrated into a broader information-rich infrastructure. Fundamental to realising this goal is the extensive use of smart materials and conductive textiles, which are here reviewed. Advances in textile-based sensors and actuators are documented, as are also developments in the generation and storage of electrical power. Also addressed are the protocols and available information technologies that are relevant for integrating these products within an Internet of Things (IoT) framework. The procedures and practices for developing apparel products incorporating these technologies are discussed. Some insights into the state-of-the-art are gained from examining commercial products and the reports of interdisciplinary research projects. The conclusion is largely that we are at an early stage of realising the IoT vision, but that prototypes emerging justify an attitude of cautious optimism.